Analisis Bibliometrik dengan Pendekatan Co-Word: Memetakan Trend Penelitian Ilmu Perpustakaan di Jurnal Pustakaloka - Santoso, Budhi; Hak, Nurul; Labibah, Labibah (Institut Agama Islam Negeri Salatiga, 2024)
Science is developing rapidly, scientific developments can be seen from research conducted in scientific journals. The development of knowledge can be seen from the trend of research topics and trends at a certain time. Pustakaloka Journal is an accredited journal in the field of library and information science. This research was conducted to determine the trend of library and information scientific research. This study used library research with a bibliometric approach using Co-word analysis using VOSviewer. Based on the results of research in 2019-2022 in the last 4 years, it can be seen that there are 202 keywords and 35 clusters. The ten strongest keywords in the journal Pustakaloka: Journal of Library and Information Sciences are; Libraries (26), Library Services (20), Librarians (19), College Libraries (16), Information Needs (8), Information Literacy (8), Social Media (8), Literacy Skills (7), Literacy (6 ), Digital Literacy (6). Cluster 1 has the biggest keywords indicating the cluster theme absorbs more attention from writers in the Pustakaloka Journal. Then for related subjects are the subject of libraries, librarians, library services and college libraries.